Design, Development and Performance Evaluation of Fish Descaling Machine - Gaikwad, Nilesh N.; Ahmad, Tanbir; Yenge, Govind B.; Singh, Ajeet (Fishery Technology, 2017)
In fish post-harvest processing, one of the unitoperations involved is removal of fish scales whichis traditionally carried out by knife. The process istime consuming and cumbersome. This may alsolead to injury to the person descaling the fishes. Inthis context, a hand held fish descaling machine hasbeen designed and developed to increase the speedof descaling process, reduce the drudgery andimprove the safety of operation. The fish descalingmachine has important components such as descalinghead, flexible shaft, safety shield, 1 hp motor, ACdrive and a stand for fixing motor and A.C. drive.Four different types of innovative designs ofdescaling heads namely, diamond shaped, invertedV shaped, 13 slots and 26 slots were tested atdifferent speeds for the capacity, efficiency, energyconsumption and injuries inflicted. Performance ofthe machine was tested for two fish species usingfour descaling heads at 1440, 2000 and 2800 rpm.The diamond shaped descaling head with its uniquedesign showed maximum descaling rate at 2800rpm. The fish descaling machine reduced drudgeryin descaling operation and also reduced the timerequired in descaling from 120 to 40 s for average500 g fish vis a vis traditional hand tool in practice.There were no incidence of injuries reported toperson descaling the fishes and also no skindamages to fishes while descaling. Average energyrequirement was 0.25 kwh for the machine and anunskilled labour was required for operation. Themachine is suitable for descaling of catla and silvercarp fish species.